Next Steps in Integrative Biology: Mapping Interactive Processes Across Levels of Biological Organization. (14th July 2021) - Cavigelli, Sonia; Leips, Jeff; Xiang, Qiu-Yun (Jenny); Lemke, Dawn; Konow, Nicolai
Synopsis: Emergent biological processes result from complex interactions within and across levels of biological organization, ranging from molecular to environmental dynamics. Powerful theories, database tools, and modeling methods have been designed to characterize network connections within levels, such as those among genes, proteins, biochemicals, cells, organisms, and species. Here, we propose that developing integrative models of organismal function in complex environments can be facilitated by taking advantage of these methods to identify key nodes of communication across levels of organization. Mapping key drivers or connections among levels of organization will provide data and leverage to model potential rule-sets by which organisms respond and adjust to perturbations at any level of biological organization.